2016
DOI: 10.11002/kjfp.2016.23.7.977
|View full text |Cite
|
Sign up to set email alerts
|

Identification of volatile flavor compounds in Jeju citrus fruits

Abstract: The volatile flavor compounds in five Jeju citrus fruit varieties (Cheonhyehyang, Hallabong, Jinjihyang, Hwanggeum hyang and Redhyang) were extracted by simultaneous distillation-extraction (SDE) using solvent mixture of n-pentane and diethyl ether (1:1, v/v) and analyzed by using gas chromatography-mass spectrometry (GC-MS). The number of aroma compounds were identified with : 104 (4,939.77 mg/kg) in Cheonhyehyang, 98 (3,286.38 mg/kg) in Hallabong, 105 (3,317.56 mg/kg) in Jinjihyang, 102 (4,293.39 mg/kg) in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
2
Order By: Relevance
“…Hong & Kim (2016a) reported that limonene (42.57%), sabinene (6.61%), linalool (5.17%), decanal (3.73%), limonene-10-ol (3.01%), 4-terpineol (2.65%), β-myrcene (2.58%), and β-pinene (2.32%) were detected in the essential oil of Cheonhyehyang peels. Although, ethyl benzene, nonanol, 1-p-menthen-9-al, (E) isocarveol, methyl salicylate, and α-terpinen-7-al were unique volatile fragrance components found only in Cheonhyehyang (Hong & Kim, 2016a), these were not detected in this study. Chunhyehyang peel essential oil contains 2.54 to 4.39 times more linalool than the other four citrus fruits (Table 2).…”
Section: Composition Of Essential Oil In Cheonhyehyang [(((Unshiu × C Sinensis))× C Reticulata) × (C Reticulata × C Sinensis)] Peelscontrasting
confidence: 61%
See 4 more Smart Citations
“…Hong & Kim (2016a) reported that limonene (42.57%), sabinene (6.61%), linalool (5.17%), decanal (3.73%), limonene-10-ol (3.01%), 4-terpineol (2.65%), β-myrcene (2.58%), and β-pinene (2.32%) were detected in the essential oil of Cheonhyehyang peels. Although, ethyl benzene, nonanol, 1-p-menthen-9-al, (E) isocarveol, methyl salicylate, and α-terpinen-7-al were unique volatile fragrance components found only in Cheonhyehyang (Hong & Kim, 2016a), these were not detected in this study. Chunhyehyang peel essential oil contains 2.54 to 4.39 times more linalool than the other four citrus fruits (Table 2).…”
Section: Composition Of Essential Oil In Cheonhyehyang [(((Unshiu × C Sinensis))× C Reticulata) × (C Reticulata × C Sinensis)] Peelscontrasting
confidence: 61%
“…Limonene (84.46%), sabinene (3.12%), β-myrcene (1.83%), linalool (1.57%), and β-ocimene (1.29%) were the major components of the essential oil of Hallabong peel. Hong and Kim (Hong & Kim, 2016a) reported 96 compounds, including limonene (62.18%), β-myrcene (5.65%), α-pinene (2.49%), ethyl acetate (1.26%), and β-pinene (1.92%), from Hallabong peel essential oil. The essential oil composition of Hallabong peel in the previous study was similar to that in this study.…”
Section: Composition Of Essential Oil In Hallabong [(C Unshiu Marc× C Sinensis Osb)×(c Reticulata Blanco)] Peelsmentioning
confidence: 99%
See 3 more Smart Citations